Subsídios para implantação do processo de compostagem em município de pequeno porte: estudo de caso em Corumbataí-SP - Aquino, Lucilene de (Universidade Federal de São Carlos, 2012)
University of São Carlos, 2012. Composting is one of the oldest processes of recycling organic waste. Despite being an environmentally appropriate treatment, their use is still little known regarding the management of municipal solid waste (MSW). This study aimed to investigate the management of MSW in Corumbataí - SP. For this purpose gravimetric characterization of MSW were performed, and composting alternatives applicable to the municipality of Corumbataí were analyzed. The study also sought to assess the perception inhabitants of the city regarding the subject matter, as well as their acceptance regarding previous separation of compostable organic waste (COW). Initially a survey on the management from the MSW was implemented. Two gravimetric characterizations were carried out, being the first in June and the other in December. In order to choose the composting alternative the following aspects were analyzed: the amount of organic waste; the availability and accessibility of the area; the existing infrastructure, equipment, labor and impacts on the environment. Questionnaires were applied to each of the families, from house to house, in order to evaluate the existing selective collection program, as well as the amount of knowledge they had about composting. The level of their acceptance in doing separation of organic household waste was also evaluated. Results: We found that the public power is adapting its MSW in a way environmentally responsible, and the selective collection program has shown good efficiency. Through gravimetric characterizations performed in the months of June and December, we obtained a high percentage of organic material (80%), identifying thus the viability of implementing a composting process. We found that the public power is adapting its MSW in a way that is environmentally correct, and the selective collection program has shown a good efficiency. About gravimetric characterizations performed in the months of June and December, we obtained a high percentage of organic matter (80%), identifying the availability of implementing a composting process. It was suggested the use of manual system of rotated furrows because of simple technology, constituted from equipment of easy maintenance and low cost. The research performed with the population found that 100% of respondents participate on the selective collection and had no doubt about the process of waste unbundling. In addition, garbage collection services provided by municipal employees were rated as excellent and good in 89% of the interviewed. About composting, 51% of the respondents had knowledge about the subject, as well as waste that could be composted. Another important finding of this study was to observe that 98% of the interviewed are disposed to separate organic waste for composting. The statement of a significant percentage of organic matter present in the composition of the MSW from Corumbataí means to provide a final destination for the most noble organic waste, with composting as an alternative for the treatment of them. Since the practice of selective collection is incorporated into the habits of the population, there is a positive perspective on the introduction of a third separation for composting organic waste (ROC) as observed in the research about the knowledge and opinion of locals about composting. In this sense it was suggested that the manual system using plowed furrows because of the simplified technology, comprising equipment for easy maintenance and low cost. The survey conduct among the population found that 100% of the respondents participate in the selective collection and have no doubts about the process of separating the trash. Furthermore, 89% of respondents the garbage collection services provided by municipal employees were rated as excellent or good. As for composting, 51% of respondents had knowledge about it, and knowing identify which waste could be composted. Another important fact observed in the study was that 98% of respondents are willing to separate organic waste for composting.
Subsidies for the implementation of the composting process in a small municipality. Case study: Corumbataí-SP
Keywords: Engenharia urbana; Coleta seletiva; Resíduos sólidos; Solid waste; Separate collection; Composting; ENGENHARIAS